2008
DOI: 10.1097/iae.0b013e3181853d3c
|View full text |Cite
|
Sign up to set email alerts
|

Transconjunctival 25-Gauge Sutureless Vitrectomy and Silicone Oil Injection in Diabetic Tractional Retinal Detachment

Abstract: Pars plana vitrectomy and 1,000 centistokes silicone oil injection with 25-gauge system is feasible in diabetic tractional retinal detachment even in complex cases. Indications of 25-gauge surgery may be expanded toward this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
4
34
1
Order By: Relevance
“…This drawback can be avoided by the use of a special 25-G cannula for silicone oil injection, as reported by Altan et al [18] or even by the use of a 24-G angiocatheter with a rigid 25-G stylet needle as reported by Riemann et al [19]. We encountered iatrogenic retinal tears in 31.5% of cases that needed membrane dissection.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This drawback can be avoided by the use of a special 25-G cannula for silicone oil injection, as reported by Altan et al [18] or even by the use of a 24-G angiocatheter with a rigid 25-G stylet needle as reported by Riemann et al [19]. We encountered iatrogenic retinal tears in 31.5% of cases that needed membrane dissection.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies that reported the outcomes of 25-G TSV in these conditions included a limited number of cases [3,18,[21][22][23][24]. The purpose of this study is to evaluate the efficacy and safety of 25-G TSV for the management of PDR.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies were limited in size, retrospective, and utilized primarily silicone oil. 6,7,[17][18][19] However, a prospective, randomized study by Kumar and colleagues compared the visual and anatomic success rates of 23-G versus 25-G PPV with C3F8 or silicone oil tamponade for repair of diabetic TRD (25 eyes in both groups). Complication rates were similar, and anatomic success was achieved in all 50 eyes in the study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Given the benefits of 25-G systems, several studies have investigated its use in the treatment of complicated retinal detachment, including diabetic TRD; comparable outcomes and complication rates between 25-G PPV and 20-G or 23-G systems have been found. 6,7,[17][18][19][20] However, these studies included limited numbers of TRD eyes and only evaluated silicone oil or octofluoropropane (C3F8) tamponades. This study aims to evaluate the effectiveness of 25-G PPV and a variety of tamponade agents in a large population of eyes with diabetic TRD, many of which also had combined rhegmatogenous retinal detachments (RRD) or PVR.…”
Section: Introductionmentioning
confidence: 99%